Sport, Modernity & Nation Building: The Indonesian National Games of 1951 and 1953 - Brown, Colin (KITLV (Koninklijk Instituut voor Taal -, Land- en Volkenkunde), 2008)
The study of sport – its social, political, cultural and economic aspects – is a well-established academic field, scholars widely acknowledging its significance in understanding how a society is organized and understood. As Perkin (1992:211) puts it: The history of societies is reflected more vividly in the way they spend their leisure than in their politics or their work […] the history of sport gives a unique insight into the way a society changes and impacts on other societies it comes into contact with and, conversely, the way those societies react back to it. Sport has a particular resonance in considerations of the emergence of modern nation-states out of colonialism, given the connections between the diffusion of modern sports around the world and the colonial experience. Although virtually all societies played games of various kinds, competitive, rule-based sports are essentially modern, western phenomena, dating back no further than the nineteenth century. Their spread through the world coincided with, and in many respects was an inherent part of, the expansion of western colonialism. In the British Empire in particular, sport was seen as reflecting the essential values and characteristics of the British race which justified the existence of colonialism. Wherever the British went, they took their sports with them, together with the social mores they represented.